2023
DOI: 10.1002/fsn3.3427
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin gallate (EGCG) inhibits lipopolysaccharide‐induced inflammation in RAW 264.7 macrophage cells via modulating nuclear factor kappa‐light‐chain enhancer of activated B cells (NF‐κB) signaling pathway

Abstract: Epigallocatechin‐3‐gallate (EGCG) is a major bioactive compound in tea polyphenol extract. After ingestion, EGCG reaches the intestine and may commence anti‐inflammation in the intestinal organ. Thus, in this paper, the anti‐inflammatory effect of EGCG was studied using lipopolysaccharide (LPS)‐induced inflammation in RAW 264.7 cells. LPS induction instigated morphological deformation extensively which was normalized by EGCG. In LPS‐induced macrophage cells, EGCG was found to lower cellular nitric oxide (32% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…NO has been reported as a crucial mediator of inflammatory response to invading pathogens, eliminating tumor cells, and performing biological functions. The activated macrophages secrete pro‐inflammatory cytokines, such as IL‐6, IL‐1β, and TNF‐α to defend against the pathogens (He et al, 2021 ; Hossen et al, 2023 ). However, excessive production of NO and pro‐inflammatory cytokines can lead to increased tissue damage and induce serious immune dysfunction in the body.…”
Section: Discussionmentioning
confidence: 99%
“…NO has been reported as a crucial mediator of inflammatory response to invading pathogens, eliminating tumor cells, and performing biological functions. The activated macrophages secrete pro‐inflammatory cytokines, such as IL‐6, IL‐1β, and TNF‐α to defend against the pathogens (He et al, 2021 ; Hossen et al, 2023 ). However, excessive production of NO and pro‐inflammatory cytokines can lead to increased tissue damage and induce serious immune dysfunction in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Among a high number of molecules fitting this description, we can find phenolic acids, flavonoids and terpenoids, for example. To name some of the most common ones, EGCG [159,160], quercetin and its derivative rutin [161][162][163][164], luteolin and its derivatives luteolin-7-Oglucoside and luteolin-7-O-glucuronide [161,165,166], kaempferol [161], apigenin [161], eriodictyol [167], rosmarinic acid [140,164], caffeic acid [136,168], oleanolic acid [169], ursolic acid [169,170], or carvacrol [171] are examples.…”
Section: The Role Of Macrophages In Oxidative Stress and Inflammation...mentioning
confidence: 99%
“…More importantly, the intervention effects of the selected nutrients have been stated with the identical effects of anti-oxidative stress, anti-inflammation, and immunity enhancement, etc. ; in particular, a large number of studies have shown that these compounds have excellent functions in immune regulation, such as reducing the release of inflammatory factors from macrophages and potentially enlightening the enhanced intervention of their complex ( 4–6 ).…”
Section: Introductionmentioning
confidence: 99%